2010 IEEE International Conference on Acoustics, Speech and Signal Processing 2010
DOI: 10.1109/icassp.2010.5495655
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary spectral clustering with adaptive forgetting factor

Abstract: Many practical applications of clustering involve data collected over time. In these applications, evolutionary clustering can be applied to the data to track changes in clusters with time. In this paper, we consider an evolutionary version of spectral clustering that applies a forgetting factor to past affinities between data points and aggregates them with current affinities. We propose to use an adaptive forgetting factor and provide a method to automatically choose this forgetting factor at each time step.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Another example of snapshot-based approach is based on state-of-the-art spectral clustering extended by consistency constraints [17] or adaptive forgetting factor [62]. A comprehensive study of evolutionary clustering can be found in a survey by M. Spiliopoulou [54].…”
Section: Snapshot-based Community Detectionmentioning
confidence: 99%
“…Another example of snapshot-based approach is based on state-of-the-art spectral clustering extended by consistency constraints [17] or adaptive forgetting factor [62]. A comprehensive study of evolutionary clustering can be found in a survey by M. Spiliopoulou [54].…”
Section: Snapshot-based Community Detectionmentioning
confidence: 99%
“…If ε is set too large, for example 0.50, the model might incur "over-smoothing", i.e. being unable to adapt to changes in the community structure on this period [42].…”
Section: Mit Social Evolution Datasetmentioning
confidence: 99%
“…However, Ψ t is unknown in real applications so the goal is to estimate it as accurately as possible. If we take the estimate to be the convex combination defined in (1), it was shown in [13] that the optimal choice of α t that minimizes the MSE in terms of the Frobenius norm E…”
Section: Adaptive Evolutionary Clusteringmentioning
confidence: 99%
“…The algorithm involves computing the eigenvectors corresponding to the k largest eigenvalues of a normalized version ofW t , then discretizing the eigenvectors so that each node is assigned to a single community. We refer readers to [13] for additional details on the adaptive evolutionary spectral clustering algorithm.…”
Section: Adaptive Evolutionary Clusteringmentioning
confidence: 99%
See 1 more Smart Citation